1997
DOI: 10.1021/la9605293
|View full text |Cite
|
Sign up to set email alerts
|

Orientation of Cytochrome P450scc in Langmuir−Blodgett Monolayers

Abstract: Monolayers of cytochrome P450scc and its complex with adrenodoxin were formed by Langmuir techniques and covalently immobilized on the solid substrates. The orientation of hemeprotein molecules was studied using polyclonal antibodies specific to the intact cytochrome P450scc molecule and its tryptic fragments F1 and F2, representing N- and C-terminal parts of the hemeprotein molecule. Specific interactions of the Langmuir films of cytochrome P450scc with adrenodoxin were investigated, and the position of the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

1998
1998
2006
2006

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 22 publications
2
19
0
Order By: Relevance
“…A protein under such conditions normally maintains its secondary structure, but loses its original 3D conformation [10]. Different protein monolayers were found to be stable and preserve their native conformation after spreading [11][12][13]. For instance, Korenbrot and Pramik showed that the conformation of rhodopsin at an interface was similar to that found in its native environment [14].…”
Section: Introductionmentioning
confidence: 99%
“…A protein under such conditions normally maintains its secondary structure, but loses its original 3D conformation [10]. Different protein monolayers were found to be stable and preserve their native conformation after spreading [11][12][13]. For instance, Korenbrot and Pramik showed that the conformation of rhodopsin at an interface was similar to that found in its native environment [14].…”
Section: Introductionmentioning
confidence: 99%
“…A protein under such conditions normally maintains its secondary structure, but loses its original 3D conformation [19]. The degree to which protein monolayers are compressed was found to considerably affect the orientation of molecules at the interfaces [20,21].…”
Section: Proteins At Interfacesmentioning
confidence: 99%
“…Thus, among others, rhodopsin [22,23] photosystem II reaction center [24,25]. Photosystem II core complex [26,27], cytochrome P450 scc [21], myelin basic protein [28], and the serotonin transporter (SERT) [29,30] have been studied at the air/water interface. All these protein monolayers were found to be stable and to have preserved their native conformation after spreading.…”
Section: Proteins At Interfacesmentioning
confidence: 99%
“…A protein under such conditions will maintain its secondary structure but will lose its original 3D conformation [8]. The degree to which protein monolayers are compressed was found to considerably affect the orientation of molecules at the interfaces [9–11].…”
Section: Introductionmentioning
confidence: 99%
“…The preservation of the native conformation of a spread protein can be confirmed either by size calculations or by biological assays which generally show that the protein activity remains intact. Thus, among others, rhodopsin [9], cytochrome P450 scc [11] and myelin basic protein [12] have been shown to maintain their original 3D size and were not denatured upon spreading at the air/water interface. In their pioneering work, Korenbrot and Pramik [13] have suggested that the conformation of rhodopsin at the interface is similar to that in its native environment.…”
Section: Introductionmentioning
confidence: 99%